Relative density correlations are not reliable criteria - Hamidi, Babak; Varaksin, S.; Nikraz, Hamid (ICE Publishing, 2013)
The concept of relative density was developed with the intention of appropriately defining looseness and denseness of sand or sand–gravel soils in a meaningful way; however, there are sufficient amounts of research and case studies to demonstrate the unreliability of this concept due to its large inherent errors. Nevertheless, this parameter found its way early on as a ground improvement acceptance criterion based on the same philosophy that led to its formation. As there was general agreement among engineers that, in any case, direct testing of relative density in actual deep ground improvement projects was difficult, time consuming and costly, direct methods of relative density measurement were abandoned in favour of correlation to other field tests. At first glance, this may have seemed to work out quite well as the conceptual unreliability of relative density did not come into play, but a deeper look could reveal that the proposed correlations are also as unreliable as the concept itself. This paper will discuss the reasons why relative density correlations should not be used as ground improvement acceptance criteria, and alternative reliable criteria will be proposed.